SWAT model application for simulating water balance and water yield in the lower Sutlej sub-basin - SHARMA, NAVNEET; KAUSHAL, ARUN; YOUSUF, ABRAR (Journal of Soil and Water Conservation, 2023)
Understanding the various components of water balance and water yield are necessary for planning and management of a river basin. The present study evaluated the water balance components of lower Sutlej sub-basin (8620.40 km2) of India using the soil and water assessment tool (SWAT) hydrologic model. The river basin was delineated to 15 watersheds encompassing 631 hydrologic response units (HRUs). Monthly calibration (2011–2016) and validation (2017–2021) of the SWAT model were carried out using observed discharge data. The fairly good agreement was observed between measured and simulated monthly discharge with coefficient of determination of 0.76 and Nash–Sutcliffe efficiency of 0.76, percent bias of -2.30, index of agreement of 0.93, Ratio of RMSE to the standard deviation of the observations of 0.49, Kling-Gupta efficiency of 0.82 for calibration and 0.75, 0.67, 0.10, 0.93, 0.57 and 0.80 respectively for validation. The model exhibited good performance in simulating the runoff patterns over the study period, verifying its appropriateness for future applications. The water balance components viz., surface runoff, lateral flow, base flow and ET were computed as 31.52%, 7.1%, 9.40% and 50.22% of average annual rainfall during calibration and 30.48%, 6.55%, 7.73%, and 49.98% during validation, respectively. The average annual water yield was computed as 469.31 mm (48.41%) and 420.71 mm (46.39%) during calibration and validation, respectively. This study concluded that the SWAT model could be used as a decision support system for the sustainable management of water resources.